Beyond the Limit: Salvaging the Posterior Circulation Territory via Late Endovascular Thrombectomy - Aliñab, Ryan; Soliven, Jo Ann; Jocson, Victor Erwin; Sarapuddin, Gemmalynn (Case reports in neurology, 2025)
Introduction: Posterior circulation infarctions, particularly basilar artery occlusions, contribute significantly to morbidity and mortality in ischemic stroke. However, literature supporting mechanical thrombectomy in the posterior circulation, especially beyond the 24-h window, is limited. Case Presentation: We present the case of a 64-year-old male diagnosed with basilar artery occlusion who underwent a successful mechanical thrombectomy 11 days after symptom onset. Despite complications such as hemorrhagic transformation and herniation, the patient was stabilized and showed functional improvement 3 months post-stroke. Conclusion: This case suggests that delayed thrombectomy may provide benefits for selected patients, even beyond the recommended 24-h window. Further research is essential to refine treatment strategies and potentially extend the intervention window for posterior circulation strokes.